(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
The esterification of sucrose with stearic, palmitic and oleic acids yields the corresponding esters. Effective methods have been developed for carrying out the esterification reaction at temperatures of 150–170℃ in high-boiling aprotic dipolar solvents.